Validation of a Professional Development Model for Academic Department Heads in Universities Based on Individual Coaching Approaches - Khalili , Ali; Daneshvar Heris, Zarrin; Talebi , Behnam (Assessment and Practice in Educational Sciences, 2025)
This study aimed to design and validate a professional development model for academic department heads in Iranian universities based on individual coaching approaches. A mixed-methods exploratory design was employed, combining qualitative and quantitative methodologies. In the qualitative phase, semi-structured interviews were conducted with 14 academic experts selected through purposive sampling, and data were analyzed using grounded theory coding (open, axial, and selective coding). In the quantitative phase, a researcher-developed questionnaire based on the qualitative findings was distributed to a sample of 252 academic department heads using simple random sampling. Confirmatory factor analysis (CFA) was performed using PLS-SEM to assess the structural validity of the proposed model, alongside model fit indices including SRMR, RMS Theta, R², and f² values. Confirmatory factor analysis demonstrated strong and statistically significant factor loadings across all six components of the model—causal conditions, contextual conditions, intervening conditions, core phenomenon, strategies, and consequences. SRMR and RMS Theta values confirmed acceptable model fit across all components. R² values ranged from moderate to high (0.472 to 0.831), indicating substantial explanatory power, while f² effect sizes confirmed that most constructs had large or very large influence on their respective outcomes. Among all components, the consequences and core phenomenon dimensions showed the highest predictive validity, particularly in improving managerial competencies, fostering motivation, and enhancing organizational learning. The findings validate the proposed individual coaching-based model as an effective framework for the professional development of department heads in higher education. The model is theoretically grounded, empirically supported, and practically applicable, offering universities a structured path toward leadership capacity building. Its implementation could contribute significantly to institutional improvement, faculty engagement, and sustainable academic governance.